Two-year outcome of quality of life among heroin dependants at Methadone Maintenance Therapy clinic, Hospital Tengku Ampuan Afzan - Musa, Ramli; Abu Bakar, Ahmad Zafri; Mat Zain, Nora; Mohamed Rozali, Junid (Malaysian Medical Associations, 2010)

(untitled)
The commencement of Methadone Maintenance Therapy (MMT) in 2005 has made a quantum leap in the management of heroin dependence in Malaysia. The objective of the study was to examine the two year change in quality of life (QOL) among heroin dependants at MMT clinic, Tengku Ampuan Afzan Hospital (HTAA).This was a cohort study in which the second administration of QOL was conducted with two year interval from the baseline. From a total of 172 patients enrolled into the MMT programme at the point of entry at HTAA, we examined 107 patients who were retained in the programme after two years(62.6% retention rate). Analysis of repeated measurement of paired t-test demonstrated significant imrovements in all four domains of QOL (physical, psychological, social relationships and environment) (p<0.001). The most marked improvement was noted in psychological domain.The MMT programme at HTAA is effective in improving the QOL among heroin dependants.